Fatores associados às mortes por COVID-19: um olhar sob a ótica do capital humano - Leite, Adinésia Lima (2022)
In 2020 the world was surprised by the COVID-19 Pandemic, caused by the SARS-Cov-2 virus, which triggered a global humanitarian, economic and social crisis. In this sense, this study aimed to analyze the effects of human capital, represented by the level of education, on deaths caused by COVID-19 in the municipalities of the Northeast Region, in two different periods of the pandemic: July 2020 and April 2021, respectively. To obtain the results, hierarchical logistic models were estimated with variables at individual and environmental levels. The results indicated that the probability of death is higher among males, with comorbidities, elderly, of mixed race/color and without education. In addition, people who received the antiviral vaccine or the vaccine against COVID-19 had a lower risk of death from the disease. The IDHM also showed significance in reducing the probability of deaths. However, the basic sanitation and per capita income variables were not significant. Therefore, in the case of municipalities in the Northeast, it cannot be said that these two variables had a significant impact on the chance of death from SARS-CoV-2. Keywords: COVID-19 Pandemic; Human capital; Northeast Region.